2005
DOI: 10.1128/iai.73.4.2554-2555.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Mannose Receptor Mediates the Cellular Immune Response in Human Coccidioidomycosis

Abstract: Mannose is the predominant monosaccharide in the coccidioidal antigen preparation T27K. Mannan and anti-CD206 antibody significantly decreased the surface expression of mannose receptor (MR) on adherent peripheral blood mononuclear cells and reduced the interleukin-2 (IL-2) release induced by T27K. These data suggest that MR mediates IL-2 release by T27K.The mannose receptor (MR) is found on the surface of macrophages and dendritic cells, can bind terminal mannoses found on fungi and other pathogens (6), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The relative binding activity was expressed as optical density (OD) for each test antigen after subtracting the values from the background. To confirm the binding specificity, inhibition assays were performed with serial dilution of anti-hMR blocking antibody (3.0 µg/ml, clone 19.2, BD Pharmingen, Mississauga, Ontario), mannan (3.0 mg/ml, Sigma), a CD206 ligand [43], [44], and mannose (100.0 µg/ml, Sigma, Oakville, Ontario) added and incubated for 1 h before the allergens were added to the plates for binding assays.…”
Section: Methodsmentioning
confidence: 99%
“…The relative binding activity was expressed as optical density (OD) for each test antigen after subtracting the values from the background. To confirm the binding specificity, inhibition assays were performed with serial dilution of anti-hMR blocking antibody (3.0 µg/ml, clone 19.2, BD Pharmingen, Mississauga, Ontario), mannan (3.0 mg/ml, Sigma), a CD206 ligand [43], [44], and mannose (100.0 µg/ml, Sigma, Oakville, Ontario) added and incubated for 1 h before the allergens were added to the plates for binding assays.…”
Section: Methodsmentioning
confidence: 99%
“…Because we observed a high expression of CD206 in the presence of miR-27a-loaded EVs, we reasoned that the increase in CD206 mediated by miR27a might be responsible for the increased phagocytosis. We used mannan, a CD206 ligand, and anti-CD206 (␣-CD206), a monoclonal antibody directed against CD206, to block the surface expression of CD206 on the monocytes and examined the effect of miR-27a-loaded EVs on naive monocytes (50). We observed that both mannan and ␣-CD206 treatment led to a significant decrease in the phagocytic activity of monocytes (Fig.…”
Section: Mir-27a-loaded Evs Have Functional Effects On Naivementioning
confidence: 99%
“…However, prior studies using T27K as the antigen preparation have demonstrated specificity. For example, we found that the number of CD3 ϩ lymphocytes producing intracellular IFN-␥ was significantly higher from samples from previously identified healthy immune donors than from nonimmune healthy donors (8) and was higher than with donors with active, disseminated coccidioidomycosis (4). In addition, we have been able to induce a specific in vitro coccidioidal cellular immune response in lymphocytes from both nonimmune healthy donors and from nonreactive individuals with active coccidioidomycosis using mature dendritic cells incubated with T27K (25).…”
Section: Discussionmentioning
confidence: 84%
“…Currently, there are no defined coccidioidal antigens available that have been shown to be immunogenic in humans. Moreover, defined antigens, particularly those that are genetically cloned, may be less immunogenic than preparations derived directly from the organism, such as T27K, because the latter are highly glycosylated, allowing for attachment to innate receptors, such as that for mannose (8).…”
Section: Discussionmentioning
confidence: 99%